Pengaruh Customer Experience, Electronic Word Of Mouth, Kualitas Produk, Dan Strategi Pemasaran Terhadap Niat Pembelian (Studi Pada Produk Executive) - Ningtyas, Sindi Wahyu; Primanto, Alfian Budi; Dianawati, Eris (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to explore and evaluate the effects of customer experience, electronic word of mouth (e-WOM), product quality, and marketing strategies on consumers' purchase intention of Executive brand products. A quantitative research approach was adopted, utilizing a Likert scale for measurement. The sample, consisting of 125 students, was selected through purposive sampling using the Malhotra formula. Data collection was carried out through questionnaires distributed via Google Forms. The data analysis involved several tests, including validity and reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis testing, and the coefficient of determination test, all conducted using SPSS version 26. The findings indicate that customer experience, electronic word of mouth, product quality, and marketing strategies have both simultaneous and individual effects on the purchase intention of Executive products. Keyword: Customer Experience, Electronic Word Of Mouth, Product Quality, and Marketing Strategy, Purchase Intention